MICROSHOCKS – ACOUSTIC EMISSIONS IN THE AREA OF THE KUMTOR GOLD DEPOSIT ACCORDING TO THE DATA FROM DIGITAL SEISMIC STATION “TARAGAY” FOR 2015-2022 (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Study results on microshocks in the area of the Kumtor gold deposit based on data from the Taragay (TARG) digital seismic station are presented in the paper. Hierarchy of cycles is noted in the sequence of microshocks manifestations in 2015-2022. Available data let us assume that the source of microshocks right before the earthquake’s main shock is the inter-anomaly area - the barrier between the dynamic segments of active fault. Relatively high frequencies of microshocks occur in July - August and January. This is probably due to the melting and structuring of glaciers and snowfields in summer time and their complete accumulation in winter.
Keywords: microshock; gold deposit; arthquake; recurrence period; dynamics; seismic cycle